Penguatan sistem informasi inovasi antara strategi inovasi ekstern dan kinerja perusahaan - Asep Rokhyadi (Universitas Mercu Buana Yogyakarta, 2013)
Today’s innovation strategy needs to be observed as a dynamic strategy. Rapid changes in the externalities require the companies have smart innovation strategies with good method and information system of innovation. This research was conducted on 138 large and medium sized manufacturing companies in the province of Daerah Istimewa Yogyakarta. The aim of this study is to determine the extent to which externality innovation strategies effect on the performance of the the companies with information system of innovation as a moderating. By using a regression analysis can be proved that the company’s performance can be explained by the activity collaboration, and encouragement of innovation. There is no significant effect from sources of innovation. Moderasian regression analysis with information system shows that not all interaction variables have significant effect.